34.4k views
5 votes
Help 27 points!!!!!!!!!!!!!!!!!

Help 27 points!!!!!!!!!!!!!!!!!-example-1
User Kickaha
by
5.4k points

2 Answers

4 votes

Answer: no soulution

Step-by-step explanation

User Elmer
by
5.9k points
4 votes

Answer:

No solution

Explanation:

We can use the substitution method to solve this.

3x - 6y = -12, x = 2y + 8

Substitute: 3(2y + 8) - 6y = -12

Distribute: 6y + 24 - 6y = - 12

Simplify: 24 = -12

But because 24 ≠ -12, there is no solution.

User Brandon Wagner
by
5.6k points